2017
DOI: 10.17577/ijertv6is020079
|View full text |Cite
|
Sign up to set email alerts
|

Shear Characteristic Study of RC beams Retrofitted with FRP and Cement Matrix Composite

Abstract: The shear behavior and ductility property of beams, retrofitted with cement matrix composite and epoxy binder are compared in this study. Ten shear deficient beams were casted out of which eight beams were retrofitted. Four beams were retrofitted with epoxy binder, and remaining four beams with cement matrix composite. Glass fiber and sisal fiber were used for retrofitting. Cement matrix was prepared with silica fume and superplastisizer. The fibers were diffused in the cement matrix. Four point bending test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Thus, the increased adiposity observed in the vitamin A-supplemented group supports the fact that the effect is mediated through elevated expression of PPARγ and is associated with greater expression of leptin and other lipogenic pathway genes, including FABP and SCD1. In the present study, circulatory leptin levels were not measured, but Harishankar et al (2011) have shown hyperleptinaemia in this obese model, which supports leptin gene overexpression in RPWAT of stock diet-fed obese rats. Overall, transcriptional analysis of the vitamin A metabolic pathway and the impact of vitamin A supplementation do not tally with adiposity or the available literature.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, the increased adiposity observed in the vitamin A-supplemented group supports the fact that the effect is mediated through elevated expression of PPARγ and is associated with greater expression of leptin and other lipogenic pathway genes, including FABP and SCD1. In the present study, circulatory leptin levels were not measured, but Harishankar et al (2011) have shown hyperleptinaemia in this obese model, which supports leptin gene overexpression in RPWAT of stock diet-fed obese rats. Overall, transcriptional analysis of the vitamin A metabolic pathway and the impact of vitamin A supplementation do not tally with adiposity or the available literature.…”
Section: Discussionsupporting
confidence: 75%
“…Previously, we reported that consumption of vitamin A-enriched diet ameliorated obesity in a euglycaemic obese rat model of the WNIN/Ob strain (Jeyakumar et al 2006(Jeyakumar et al , 2008. Unlike obese WNIN/Ob rats, obese rats of the WNIN/GR-Ob strain display impaired glucose tolerance upon oral glucose loading, in addition to features of the metabolic syndrome, such as increased body weight, adiposity, dyslipidaemia, hyperinsulinaemia, hyperleptinaemia and high plasma high-density lipoprotein-cholesterol concentrations compared with their age-and sex-matched lean counterparts (Jeyakumar et al 2009;Harishankar et al 2011). However, the candidate gene(s) for obesity in this strain of rats are yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the FRP strips are most effective for medium shear span/depth ratios (1.5 to 2.5). Harishankar [14] did a comparative study of the shear behavior and ductility property of beams retrofitted by glass and sisal fiber with cement matrix composite and epoxy binder in which, ten shear deficient beams were cast, out of which eight beams were retrofitted by side bonding and two as a control. It was found that the beams retrofitted using glass fiber was showing better load carrying capacity than the beams retrofitted using sisal fibers and the Epoxy binder is more effective compared to Cement matrix composite.…”
Section: Introductionmentioning
confidence: 99%